La prévalence de l’asthme adulte chez les patients consultants au niveau de service pneumo-phtisiologie de l’EPH Frères Khatib EPH Frères Khatib «Ouled Mohammed» Chlef. - CHERRAK, Aouda (My University, 2018)
T o determine the prevalence of adult-asthma of the consulting pateints in the Pneumophysiologie departement of Ouled Mohamed's hospital/Chlef , we realised this work which is divided into two large chapiters . The first one is devoted to a bibliographic review of asthma , a problomatic, generalities, about the disease and its prevalence in the world and especially in Algeria,the risk factors, and a therapeutic education . The second , represent a cross-section study consists of 64 questionnaires addressed to the consulting patients in the Pneumophysiology department of Ouled Mohamed's hospital.During a period of 60 days starting from the eighteenth of March to the sixteenth of May 2018. After analyzing the results,it was found that the prevalence of adult asthma in our study was 22.22%of respiratory consultants , the median age was 51 years with an age range from 18 to 87years , a female predominance of 69 % and 39 % for males. From our results we found that 47 of the asthmatic subjects (73,46%) had asthma before the age of 50 years old and 17 (26,6%)had this disease after the age of 50.69% of the subjects belong to an urban population and 31% lives in the rural environment .42 patients (66%)confirms the presence of plants inside their houses .86% of the patients had asthma attacks in their daily life and this attacks were described by : often,sometimes,almost always,rarely, and after a physical activity , the results were as follows : 23,15,8,7and 2 cases. The results indicate that the hypertensionand diabetes are mostly present in the personal medical history of the patients with 14,5% and 11,6% , the comes the allergy with (10,1%) , Bronchitis and heart failure with 4,3% , goiter(2,9%) , anemia , eczema and the tuberculosis with 1,4% for each one , 47,8% of the patients did not mention any personal antecedents . And finally a conclusion about the study results and the principal recommandations
Keywords: l'asthme; problème de santé; la prévalence; les facteur de risque; étude transversale; asthma; health problem; the prevalence; risk factors; cross-sectional study